2009
DOI: 10.1007/s11274-009-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo immunostimulatory and tumor-inhibitory activities of polysaccharides isolated from solid-state-cultured Trametes robiniophila Murrill

Abstract: Crude polysaccharides extracted from successfully solid-state-cultured Trametes robiniophila (PST) showed cellular immunomodulatory and tumor-inhibitory activities in vivo. The different concentration of PST (100, 200, 400 mg kg -1 body weight) significantly enhanced immunity response in mice burden with Sarcoma 180 (S180) solid tumor. The results indicated that PST not only increased the macrophage phagocytosis and NO production, but also promoted lymphocyte proliferation and natural killer cell activity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In our acute toxic test, the safety of TM was confirmed suggesting no significant influences on animal behaviors and body organs (data not shown). Moreover, the crude nature of TM may explain its non-dose-dependent manner observed in the present experiments, which is similar to other herbal medicines [26]. …”
Section: Discussionsupporting
confidence: 71%
“…In our acute toxic test, the safety of TM was confirmed suggesting no significant influences on animal behaviors and body organs (data not shown). Moreover, the crude nature of TM may explain its non-dose-dependent manner observed in the present experiments, which is similar to other herbal medicines [26]. …”
Section: Discussionsupporting
confidence: 71%
“…Steroids are one type of components in living organisms and the importance of these as a part of a healthy diet has been emphasized in the recent dietary recommendations [ 1 ]. Different functions of steroid from plants and microorganisms, such as sitosterol, stigmasterol, campesterol, ergosterol, fucosterol have been studied including inhibiting tumor growth, cellular immune stimulating, anti-inflammatory, antioxidant and anti-diabetic properties [ 2 , 3 ]. The study of Andersson et al demonstrated that sterols could be used on the prevention and treatment of the cardiovascular and cerebrovascular diseases (CCD) through higher intake of phytosterols in a natural diet to low levels of total and LDL (low density lipoprotein)-cholesterol in the serum [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two-site sandwich ELISA were performed to quantify IL-4, IFN-γ, and TNF-α in the serum according to the manufacturer's instructions. IL-4 and TNF-α concentrations were calculated from the absorbance values by plotting the values against IL-4, IFN-γ, and TNF-α standard curves, which were performed for each assay (Jia et al, 2009). …”
Section: Cytokine Assaymentioning
confidence: 99%